Indonesia : How to Get Parents’ Attention - World Bank (Washington, DC, 2015)
A growing number of countries are reforming how schools are managed and are working to involve parents and com¬munities more directly into the school management process. The idea behind school-based man¬agement reform is that devolving responsibility to schools and to those who use the schools will improve ac¬countability, transparency and ensure that resources are allocated properly. In this way, the quality of education will improve and so will learning. However, evidence on the effective¬ness of school-based management remains mixed and parental involve¬ment is often weak. Evaluating different approaches for strengthening account¬ability and transparency in education is critical to making schools successful to improve learning. In Indonesia, the World Bank worked with the government to set up and evaluate alter¬native ways to improve parents’ knowledge of and involvement in the management of money that the government gives to schools for operational costs. The evaluation found that direct approaches, like inviting parents to a meeting or sending text messages, led to improvement in parental knowledge and ac¬tions, while sending home brochures and letters didn’t lead to any changes. As countries, including Indonesia, continue to rely on school-based management to improve accountability and learning, the evaluation shows that getting parents and communities involved, and making sure they are informed, may require more intensive efforts.